Gender and teacher training in Early Childhood Education studies - Alfonso Romero Díaz; Paco Abril Morales (Revista Electrónica Interuniversitaria de Formación del Profesorado)
This paper presents the findings of a research study funded by the European Union that aims to improve early childhood teacher training in gender-related topics. Spain has made considerable headway with the inclusion of gender mainstreaming in the political agenda. However, as we point out in this paper, this issue is still not a priority in vocational training for early childhood education. A series of qualitative interviews and a quantitative questionnaire revealed a lack of training, materials and sensitivity, all needed for the introduction of gender and sexual diversity issues.